Does spatial skills instruction improve STEM outcomes? The answer is ‘yes’ - Sorby, Sheryl; Veurink, Norma; Streiner, Scott (Learning and individual differences, 2018)
Spatial cognition has long been the subject of research in psychology and education. Individual differences in spatial ability have been found between males and females. In this study, a test of spatial cognition was administered to >3000 first-year engineering students over a five-year period. Students were divided into experimental and control groups based on a pass/fail cutoff score on the spatial test. Students who failed the test were all assigned to a 1-credit spatial skills intervention course that met for one session per week over a semester; those who passed the test were assigned to the control group. A regression discontinuity analysis was used to determine the effectiveness of the intervention. A treatment effect was found for performance in a variety of introductory courses and STEM GPAs, with a particularly positive effect in Engineering Problem Solving and Analysis. These effects were found through a discontinuity at the cutoff score, with the intervention group performing at higher levels than would be expected if they had not participated in the intervention. Retention data was also examined, and it was found that the intervention had a positive impact on the retention of women in engineering. The results of this study suggest that spatial skills instruction can also be used as a key component for improving gender diversity in the STEM fields - beyond improving course performance. •Spatial skills are important to success in STEM; however, most previous studies have been correlational.•Evidence of causality is scarce.•This study fills a gap in our understanding of the causal link between spatial training and STEM success.•Spatial skills training led to improvements in grades in a variety of STEM courses.•Spatial skills training led to improvements in STEM retention, particularly for women.